2007
DOI: 10.1021/tx600362h
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modification of Microsomal Lipids by Thiobenzamide Metabolites in Vivo

Abstract: Thiobenzamide (TB) is hepatotoxic in rats causing centrolobular necrosis, steatosis, cholestasis, and hyperbilirubinemia. It serves as a model compound for a number of thiocarbonyl compounds that undergo oxidative bioactivation to chemically reactive metabolites. The hepatotoxicity of TB is strongly dependent on the electronic character of substituents in the meta- and para-positions, with Hammett rho values ranging from -4 to -2. On the other hand, ortho substituents that hinder nucleophilic addition to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 46 publications
6
45
0
Order By: Relevance
“…Nevertheless, unlike Triapine®, the oxidation of the thiocarbonyl group plays an important role in the metabolism of Bp4eT. This is in accordance with the outcomes of in vitro and in vivo studies using other types of agents which identified oxidative desulfuration as a principle metabolic reaction for compounds containing a thiocarbonyl functional group [35][36][37]. Of interest, it has been shown that the thiocarbonyl moiety can be oxidized by flavin-containing mono-oxygenases, as well as enzymes of the cytochrome P450 superfamily [36,38].…”
Section: Resultssupporting
confidence: 70%
“…Nevertheless, unlike Triapine®, the oxidation of the thiocarbonyl group plays an important role in the metabolism of Bp4eT. This is in accordance with the outcomes of in vitro and in vivo studies using other types of agents which identified oxidative desulfuration as a principle metabolic reaction for compounds containing a thiocarbonyl functional group [35][36][37]. Of interest, it has been shown that the thiocarbonyl moiety can be oxidized by flavin-containing mono-oxygenases, as well as enzymes of the cytochrome P450 superfamily [36,38].…”
Section: Resultssupporting
confidence: 70%
“…The exact mechanism of m5 formation was not determined in the current study. On the basis of a previous report (Ji et al, 2007), an intermediate sulfate is proposed. In brief, m1 can be reduced to an alcohol, and subsequently sulfated to form a sulfate that serves as a leaving group.…”
Section: Discussionmentioning
confidence: 92%
“…Our medicinal chemistry strategy was also weighted Apart from peroxidases, enzymatic bioactivation of thioureas and related analogs (e.g., thiones, thiocarbamides, etc.) to electrophilic intermediates by mammalian P450 and/or FMO isoforms can also lead to toxicity (Poulsen et al, 1979;Neal and Halpert, 1982;Decker and Doerge, 1992;Onderwater et al, 1999Onderwater et al, , 2004Smith and Crespi, 2002;Henderson et al, 2004;Ji et al, 2007). For instance, the cases of clinical hepatotoxicity and/or nephrotoxicity that were noted with the antithyroid drug methimazole (Martinez-Lopez et al, 1962) and the antiparasitic agent thiabendazole (Manivel et al, 1987) have been causally linked with their metabolism to the proximal toxicants N-methylthiourea and thioformamide, respectively, via an initial P450-catalyzed oxidative ring scission of the 2-mercaptobenzimidazole and thiazole motifs present in these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative Desulfurization by FMOs 1267 at ASPET Journals on May 11, 2018 dmd.aspetjournals.org oxidation by FMO to the unstable sulfinic acid (R-SO 2 H), which is more reactive than the sulfenic acid metabolite and can damage the cell directly or alkylate proteins (Onderwater et al, 1999(Onderwater et al, , 2004Ji et al, 2007).…”
Section: Discussionmentioning
confidence: 99%